Prospective Study of Infertility in Humans due to Life Style Changes - PI, Sibi; AR, Chithra; MS, Christy; R, Divya; PJ, Dhanooja; NX, Elizabath; UP, Shinjisha; C, Pramod (Indian Journal of Pharmacy Practice)
Today in our world most couples will have to face a challenge of infertility in their life. Infertility is the inability to conceive a child despite attempts to become pregnant over a course of 12 months. The main objective of this study was to assess the infertility treatment in humans, to compare the prevalence of infertility in different parts of Kerala and to determine the effect of environmental factors in infertility and to establish the effectiveness of patient counseling before and after drug therapy. This study was conducted at Samad IVF hospital, Trivandrum, Sanjeevani hospital, Trivandrum and Cochin hospital Ernakulam. Aprospective chart review and patient history interview was carried out in adult patients (20-50) years of age. Study was conducted for a period of 3 months, the prospective data was collected from patient case records. The main findings of this study include, the occurrence of infertility is more in males, and the chance of getting infertility is increasing with age and urban population when compared to rural. It was also found that the environmental factors influenced the infertility, especially alcohol consumption and smoking. Long term treatment for infertility is required to get the desired benefit, social awareness and the effectiveness of drug therapy can be improved by patient education.
Keywords: Infertility; lifestyle changes